2019
DOI: 10.1542/hpeds.2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Course of Croup After Emergency Department Management

Abstract: To describe inpatient management of patients with croup admitted from the emergency department (ED). METHODS: In a multicentered, cross-sectional observational study based on retrospective chart review, we identified children 6 months to 5 years of age with a discharge diagnosis of croup. All patients were evaluated in the ED and treated with at least 1 dose of racemic epinephrine (RE) before admission. Children with hypoxia or directly admitted to the PICU were excluded. RESULTS: We identified 628 admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…While this case series is limited to only three patients, all had ≥3 total NRE treatments, dexamethasone, and additional inpatient interventions (i.e., additional NRE, BiPAP, or heliox). Inpatient interventions for croup are relatively infrequent (22.6% in one study), suggesting potentially more severe pathophysiology with COVID-19 croup versus previously described croup [ 15 ]. Pediatric croup patients who received ≥3 NRE in one children's hospital were more likely to need intensive care management [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this case series is limited to only three patients, all had ≥3 total NRE treatments, dexamethasone, and additional inpatient interventions (i.e., additional NRE, BiPAP, or heliox). Inpatient interventions for croup are relatively infrequent (22.6% in one study), suggesting potentially more severe pathophysiology with COVID-19 croup versus previously described croup [ 15 ]. Pediatric croup patients who received ≥3 NRE in one children's hospital were more likely to need intensive care management [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al found out that using steroids in children who have acute respiratory distress is safe [9]. Dexamethasone is superior to budesonide and prednisolone in the management of croup.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications regarding management of croup patients have described patient management in the emergency department, steroid and antibiotic therapy, causative organisms, and intensive care unit (ICU) management of intubated patients, [1][2][3] but detailed studies on specific airway management of children needing intubation for croup are scarce. 3 Therefore, we aimed to examine the management of patients intubated for croup in our hospital and determine the risk factors for prolonged intubation in these patients.…”
Section: Introductionmentioning
confidence: 99%